Health Technology Assessment of CEM Pulpotomy in Permanent Molars with Irreversible Pulpitis - Yazdani, Shahram; Jadidfard, Mohammad-Pooyan; Tahani, Bahareh; Kazemian, Ali; Dianat, Omid; Alim Marvasti, Laleh (Iranian Endodontic Journal, 2013)
Introduction: Teeth with irreversible pulpitis usually undergo root canal therapy (RCT). This treatment modality is often considered disadvantageous as it removes vital pulp tissue and weakens the tooth structure. A relatively new concept has risen which suggests vital pulp therapy (VPT) for irreversible pulpitis. VPT with calcium enriched mixture (VPT/CEM) has demonstrated favorable treatment outcomes when treating permanent molars with irreversible pulpitis. This study aims to compare patient related factors, safety and organizational consideration as parts of health technology assessment (HTA) of the new VPT/CEM biotechnology when compared with RCT. Materials and Methods: Patient related factors were assessed by looking at short- and long-term clinical success; safety related factors were evaluated by a specialist committee and discussion board involved in formulating healthcare policies. Organizational evaluation was performed and the social implications were assessed by estimating the costs, availability, accessibility and acceptability. The impact of VPT/CEM biotechnology was assessed by investigating the incidence of irreversible pulpitis and the effect of this treatment on reducing the burden of disease. Results: VPT/CEM biotechnology was deemed feasible and acceptable like RCT; however, it was more successful, accessible, affordable, available and also safer than RCT. Conclusion: When considering socioeconomic implications on oral health status and oral health-related quality of life of VPT/CEM, the novel biotechnology can be more effective and more efficient than RCT in mature permanent molars with irreversible pulpitis.